Parental Choice of Educational Pathways for Roma Children - Stofej, Juraj (Civilia, 2013)
The aim of this paper is to clarify the process of parental choice of educational paths starting Roma children living in socially excluded areas. From January 2011 to April 2012, I conducted a participatory action research in urban environments in the area of social exclusion in western Slovakia. The research answers the question: what is the discourse of Roma parents of pre-school education and what the choice of parents for admission to kindergarten is. The research results show parental discourse is marked above all the perception of barriers associated with living in socially excluded areas. Visions of the barriers of educational institutions have a significant impact on the actual choice of educational pathways of children. They identified some steps that parents must overcome in the decision making process for entry to kindergarten: your interest in attending a kindergarten, an awareness of the benefits of preschool education despite the barriers and committed to change. Based on the understanding of this process, low-threshold program was created to address issues related to education preschool children living in the area of social exclusion.
Keywords: Discourse of pre-school education; Choice of education; The Roma minority